Pengaruh Consumer Education Terhadap Brand Loyalty Yang Dimediasi Oleh Brand Engagement - Septiani, Yunita; Kurniawati, Kurniawati (Fakultas Ekonomi Universitas Gresik, 2022)
This study aims to find out how much influence consumer education has on brand loyalty mediated by brand engagement at the 6 (six) most coffee shops in Indonesia, namely Janji Jiwa, Starbucks, J.Co Donuts & Coffee, Dunkin Donuts, Kulo and Kopi Kenangan. The data collected is primary data, which is data collected directly by researchers to answer research problems and goals. The unit of analysis in this study is individuals, because consumer education, brand engagement, and brand loyalty analyzed are for generation Z who have made purchases in 6 (six) coffee shops with the highest number of shops in Indonesia with a sample of 200 respondents. The data collection technique used is to deploy a questionnaire with a one-shoot time horizon. The results of this study show that there is an influence of consumer education on brand loyalty mediated by brand engagement.